Introduction to a special issue on kidney development and disease. Issue 10 (2nd July 2020) - Sutherland, Megan R.
Abstract: Enriching our understanding of the anatomy of the kidneys, in development, health, and disease, has been the primary focus of Professor John Bertram's distinguished research career to date. Among other notable achievements, his landmark analyses of nephron number in over 400 human kidneys (the Monash Series), and his refinement of stereological techniques for renal structural analyses, have proven him an international leader in renal anatomy research. In this Special Issue, we (some of John's collaborators, colleagues, and former students) celebrate John's career with a series of 20 review and original research articles relevant to his expertise: (a) renal anatomy, physiology, and pathology, (b) kidney development, podocyte biology, and applications of renal stem cells, (c) renal developmental programming, and (d) contemporary methodologies in renal research; his accomplishments as a Head (Chair) of an Anatomy Department are also illustrated. We hope that this collection will serve as both an important resource, and a source of inspiration, to renal anatomy researchers and educators alike.